A Unique Interaction of IVS-I-1 (G>A) (HBA2: c.95+1G>A) with Hb Adana (HBA2: c.179G>A) Presenting as Transfusion-Dependent α-Thalassemia. (4th July 2018) - Alauddin, Hafiza; Kamarudin, Khairina; Loong, Tang Yee; Azma, Raja Zahratul; Ithnin, Azlin; Jalil, Norunaluwar; Razak, Noor-Farisah; Koh-Xuan-Rong, Danny; Ismail, Endom; C-Khai, Loh; Abdul Latiff, Zarina; Alias, Hamidah; et al.
Abstract: Nondeletional α-globin mutations are known to cause more serious clinical effects than deletional ones. A rare IVS-I-1 (G>A) ( HBA2 : c.95+1G>A) donor splice site mutation interferes with normal splicing of pre mRNA and results in activation of a cryptic splice site as well as a frameshift mutation. Hb Adana [ HBA2 : c.179G>A (or HBA1 )] is a highly unstable variant hemoglobin (Hb) resulting from a mutation at codon 59 on the HBA2 or HBA1 gene, recognized to cause severe α-thalassemia (α-thal) syndromes. We report a unique case of compound heterozygosity for these two mutations in a 9-year-old boy who presented with a Hb level of 5.3 g/dL and hepatomegaly at the age of 15 months. He required regular blood transfusions in view of a Hb level of <7.0 g/dL and failure to thrive. He had thalassemic red cell indices and peripheral blood film. The Hb electrophoresis only showed a raised Hb F level (3.3%) and a pre run peak but the Hb H inclusion test was negative. His father had thalassemic red cell indices but a normal Hb level. His mother had almost normal Hb levels and red cell indices. Hb Adana involving the HBA2 gene was detected by mutiplex amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) in the proband and his father. DNA sequencing of the HBA2 gene confirmed the IVS-I-1 mutation in the proband and his mother. This case highlighted the unique interaction of the IVS-I-1 mutation with Hb Adana in a young Malay boy presenting with transfusion-dependent α-thal.